Adolescents in Foster Care: Emotional Environment in Foster Families - Shulga T.I; Antipina M.A (Moscow State University of Psychology and Education, 2018)
The article reveals the specifics of professional activities of specialists that support foster families taking care of adolescents.The outcomes of our study allow us to compare the emotional environment in foster families and families of origin (birth families).For the first time we have identified the criteria of the family emotional environment that affect adopted adolescents.The emotional attitude of adopted and biological adolescents towards the mother and father and other members of the family differs in a number of ways.Late adolescents usually lack the feeling of psychological comfort in the family as they are often overwhelmed by sadness.In foster families as well as in birth families the attitude to mothers is more positive as compared to the attitude to fathers and other family members.It is argued that a positive image of the foster mother in adopted adolescents forms the basis for their positive emotional well-being and feeling of being safe, which enables them to socialize.Spending quality time together plays an important role in creating the emotional environment, and that is true both for foster families and for families of origin.